Turbulent length scales and budgets of Reynolds stress-transport for open-channel flows; friction Reynolds numbers Reτ = 150, 400 and 1020. Issue 1 (2nd January 2021) - Ahmed, Umair; Apsley, David; Stallard, Timothy; Stansby, Peter; Afgan, Imran
Abstract : Turbulence in open channel flows is ubiquitous to hydro-environmental applications and has recently increased in importance with the deployment of tidal stream turbines, as turbulence impacts both the turbine performance and the blade fatigue life. Tidal turbine analysis requires fully developed turbulence characteristics at the inlet of numerical simulations where generally the length scale information is limited. In this study, fully resolved large eddy simulations (LES) with flat beds were undertaken using an open source code at friction Reynolds numbers ( R e τ ) of 150, 400 and 1020. It was found that the effects of the free surface on turbulence length scales were felt in approximately the uppermost 10% of the channel only, although the influence on Reynolds stresses extended further downwards. Furthermore, the cross-correlation length scales of both streamwise and spanwise velocities were found to be significantly affected by the free surface where turbulent eddies were flattened to the two-component limit.